Sociopolitical Externalities Impacting Worker Health in Washington State's Cannabis Industry. Issue 7 (30th November 2019) - Ehrlich, Trecia; Simpson, Christopher; Busch Isaksen, Tania
Abstract: Objectives: The legalization of the production, sale, and possession of cannabis in Washington State in 2012 not only created the framework for a new legal industry, but also for a new regulated labor sector. In addition to typical occupational health and safety hazards associated with chemical and physical exposures, the transition from an illicit to a regulated workplace, the inconsistency between state and federal law, and the production of a unique psychoactive commodity crop that maintains value in the illicit marketplace creates a unique work environment with workplace concerns that are political, economic, and social in nature. Methods: We conducted a combination of semistructured key informant interviews targeted toward employers, focus groups that engaged employees, and an online survey with cannabis business owners and employees to identify concerns relating to worker health and safety. Results: In addition to physical and chemical hazards related to their workplace, workers described health concerns that were a result of social, economic, and political forces facing the transitioning cannabis industry and resulting from an inconsistency between state and federal law. Important themes that emerged from these data included the legal and regulatory environment that the cannabis industry faces, cannabis as an agricultural good, crime, gender, cannabis consumption in the workplace, changing worker demographics, and emerging technologies in this rapidly evolving industry. Conclusions: The unique sociopolitical challenges for occupational health and safety that we identified among cannabis workers in Washington State are especially relevant as other states and nations follow the example of Washington State in legalizing the widespread commercial cultivation, sale, and use of cannabis. As other states and nations legalize, it will be important for employers, public health practitioners, and regulators to recognize how transitioning from an illicit to a legal marketplace impacts worker health. Further, understanding the challenges that result in transitioning a cannabis workforce may be extrapolated in the future to better understand how transitioning other goods and services from an unregulated to a regulated marketplace may impact worker health.